Formulação e caracterização de massas de grês porcelanato preparadas a partir de matérias-primas naturais do Rio Grande do norte e com adição de chamote de telhas - Melo, Maxymme Mendes de (2006)
Traditional ceramics have an important role in the economy of Rio Grande do Norte. The local industries manufacture over 50 million shingles a month, corresponding to 60% of their overall production. As a result of processing flaws, roughly 20% of the production must be discarded, since little or no use has been envisaged for such fired components. Therefore, the use of this kind of residue, especially in the composition of other ceramic materials, comes as an interesting option from the economical and environmental point of view. In this scenario, the objective of the present study was to assess the effect of the addition of fired shingle waste in the composition of porcelainized stoneware tiles. To that end, two porcelainized stoneware tiles compositions were initially prepared. Subsequently, contents from 10 to 30% of roofing tiles chamote were added to each one of them. All raw materials and grog were characterized by FRX, XRD, and thermal analysis. The ceramics were fired using natural gas for 30 min at different temperatures, i.e. 1150, 1200 and 1250ºC, and fully characterized. The addition of roofing tiles chamote resulted in composition with superior properties compared to additive-free compositions. Porcelainized stoneware tiles products that fulfill required standards for practical applications were achieved